Can corporate ESG practices promote consumers’ purchase intention of green food? The mediating role of brand trust - Li, Youyou; Chen, Xiaoya (Frontiers in Sustainable Food Systems, 2025)
This study aims to explore how corporate environmental, social, and governance (ESG) practices influence consumers’ purchase intention of green food through the mediating mechanism of brand trust. Drawing on signaling theory and stimulus–organism–response (S-O-R) theory, this research develops a conceptual model illustrating the relationships among ESG practices, brand trust, and purchase intention. Structural equation modeling (SEM) was employed to empirically test the model based on survey data collected from Chinese consumers. The findings indicate that environmental, social, and governance dimensions of ESG practices significantly and positively influence brand trust; brand trust, in turn, positively affects consumers’ purchase intention. Moreover, brand trust partially mediates the relationship between each ESG dimension and consumers’ purchase intention. This study clarifies the critical psychological role of brand trust linking ESG practices and consumer behavior, enriching the theoretical understanding of ESG research within consumer behavior literature, and providing actionable managerial insights for green food enterprises on enhancing consumers’ brand trust and purchase intention through effective ESG practices.